Study of general practice consultations and menopausal problems. Oxford General Practitioners Menopause Study Group. Issue 6771 (2nd February 1991) - Barlow, D H; Brockie, J A; Rees, C M
Abstract : OBJECTIVE--To investigate the nature of work related to the menopause in general practice. DESIGN--Questionnaire study over six months among general practitioners after each consultation with a woman aged 40-69 at which issues related to the climacteric had been discussed. SETTING--9 General practices in the Oxford area. SUBJECTS--416 Women who had 572 consultations. MAIN OUTCOME MEASURES--Age, menopausal state, and first or subsequent consultation. Symptoms were classified together with the treatment and the outcome of the consultation. RESULTS--The consultation rate varied greatly between practices, the overall rate being 4.4%. There were many premenopausal women and women in their 60s presenting; women with hysterectomies presented more often--36% (37/103) of women with hysterectomies had more than one consultation compared with 26% (38/144) for premenopausal women and 24% (38/155) for postmenopausal women. 409 women had symptoms and 218 were prescribed oestrogen treatment. 156 of the consultations involved discussion and advice only. Only four women were referred to a local specialist clinic. CONCLUSION--There is a low overall use of hormone replacement therapy in the general postmenopausal population despite the recent media coverage of its benefits in the prevention of osteoporosis and subsequent fractures.